Uptake, metabolism and subcellular distribution of [125I]T4 in calf thyroid slices - Chazenbalk, G. D.; Kleiman de Pisarev, D. L.; Juvenal, Guillermo Juan; Pisarev, Mario Alberto (1984)
Fil: Chazenbalk, G. D. Comisión Nacional de Energía Atómica; Argentina